The Relationship Between Maternal Employment and The Development of Children Toddler 1-3 Years of Age in The Working Area Puskesmas Kalabbirang, Minasatene Sub-district, Pangkep District - Rukayah, Siti; Kristina, Yunita; Ningsih, Warti; Wuriani, Wuriani; Pella, Yosin Herloheti; Ariyanti, Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Development is the increase in ability (skill) in more complex body structures and functions in a regular and predictable pattern, as a result of the maturation process. Here it involves the process of differentiation of body cells, body tissues, organs, each of which can fulfill Function: Research Objective: To determine the relationship between mother's work and the development of children aged toddlers (1-3 years) in the working area of the Kalabbirang health center, Minasatene sub-district, Pangkep district. Analytical Survey research design with a Cross Sectional study approach. Samples were drawn using purposive sampling technique from 32 respondents. The data collection technique uses a questionnaire. The collected data was processed using the Chi-Square statistical test using the computer program SPSS version 11.5. In general, it can be concluded that based on the results of the research conducted, several suggestions can be made to related parties regarding the relationship between maternal employment and the development of toddler children aged 1-3 years. For the Kalabbirang Community Health Center, Minasa te'ne District, Pangkep Regency, so that in this case the nursing staff who carry out nursing care can pay attention to the impact where patients experience conditions where there is a threat of serious illness and a care environment that makes patients feel isolated from other people so as to prevent stress from occurring. and the patient's psychological problems.